Culture of Corruption and Symbolic Rationality of Accounting Information – Higher Education Implication - Imam Wahyudi (Universitas Hayam Wuruk Perbanas, 2021)
When corruption becomes daily and socially acceptable practices, the functions of financial accounting have shifted from the instrument of managerial responsibility to a symbolic rationality of actions. Professional organizations of accountants and educational institutions consider this phenomenon as an ethical issue and have made professional ethics a mandatory subject for accounting students. This study aim to gain a better understanding of the role of accounting information in a corrupt society. It also tries to gain a better understaning that the accounting higher education institutions should play their role in this context. This study uses an interpretive phenomenological approach for the analysis. It is noted that it stresses the need for higher education institutions to take additional action by criticizing accounting principles that are fundamentally very capitalistic, being more flexible to different schools of thought, and incorporating the values of divinity into all accounting subjects.